Identification and Characterization of EI (Elongated Internode) Gene in Tomato (Solanum lycopersicum) - Sun, Xiaorong (Int J Mol Sci, 2019)
Internode length is an important agronomic trait affecting plant architecture and crop yield. However, few genes for internode elongation have been identified in tomato. In this study, we characterized an elongated internode inbred line P502, which is a natural mutant of the tomato cultivar 05T606. The mutant P502 exhibits longer internode and higher bioactive GA concentration compared with wild-type 05T606. Genetic analysis suggested that the elongated internode trait is controlled by quantitative trait loci (QTL). Then, we identified a major QTL on chromosome 2 based on molecular markers and bulked segregant analysis (BSA). The locus was designated as EI (Elongated Internode), which explained 73.6% genetic variance. The EI was further mapped to a 75.8-kb region containing 10 genes in the reference Heinz 1706 genome. One single nucleotide polymorphism (SNP) in the coding region of solyc02g080120.1 was identified, which encodes gibberellin 2-beta-dioxygenase 7 (SlGA2ox7). SlGA2ox7, orthologous to AtGA2ox7 and AtGA2ox8, is involved in the regulation of GA degradation. Overexpression of the wild EI gene in mutant P502 caused a dwarf phenotype with a shortened internode. The difference of EI expression levels was not significant in the P502 and wild-type, but the expression levels of GA biosynthetic genes including CPS, KO, KAO, GA20ox1, GA20ox2, GA20ox4, GA3ox1, GA2ox1, GA2ox2, GA2ox4, and GA2ox5, were upregulated in mutant P502. Our results may provide a better understanding of the genetics underlying the internode elongation and valuable information to improve plant architecture of the tomato.